HUMAN CHRONOTOPE IN THE NOVELS OF ISAJON SULTAN (Scientific journal of the Fergana State University, 2024)
The term "human chronotope" entered the chronotopology because the understanding of existence, the thinking of the world based on fields and branches of science is formed on the basis of human thinking. The creation of a work of art is based on the view that it is manifested in the form of the chronotope of the author and the hero.